THE INFLUENCE OF QUANTUM TEACHING MODEL ON THE STUDENT STUDY RESULTS OF SUBJECT THE USE OF MECHANIC MEASUREMENT DEVICES IN THE TENTH GRADE OF TKR SMK KARSA MULYA PALANGKA RAYA 2014/2015 - Abdul Nurohman; Debora (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2016)
The teaching learning process done by teacher plays important role of its success, but some of them still see it as just a knowledge transfer from teacher to student. Sometimes learning strategy used was just to give information and teacher-centered without involving the students to be active in the process. So, the teacher found his/her student sleeping or playing around during the class resulting their low study result in the subject Basic Job of Automotive. This research purpose is to know the difference of the teaching model Quantum Teaching and direct teaching on the study result of subject Basic Jobs of Automotive of Tenth Grade student of TKR SMK karsa Mulya 2014/2015. Based on the research results, it is known that there is a different study result when students taught with Quantum Teaching model in the posttest of experiment group where the average is 77,21 while the kontrol group had 68,25. From the normality test the data was found normally distributed for both group. For the t test, the tcalc > ttable (3,11 > 1,7). Hence, Ho is rejected and Ha is accepted. It is concluded that there is a difference in the study result students taught by Quantum Teaching model and by direct teaching on the material The Use of mechanic measurement devices in the Tenth Grade Student of TKR SMK Karsa Mulya Palangka Raya